UPAYA PENINGKATAN KEMAMPUAN PENGUASAAN BAHASA INGGRIS DI DESA PUSEURJAYA - Santika, Tika; Pujiawati, Nia; Wigati, Fikri Asih; Wahyuna, Yuna Treasna (Majalah Ilmiah SOLUSI, 2011)
The globalization which makes world become borderless encourages the students in Indonesia to learn English well. Therefore, this community service is aimed at facilitating and helping the student living in Desa Puseurjaya especially the students of SMA Negeri I Telukjambe to improve their abilities and at the same time to solve the problems they found in acquiring English as a foreign language. This community service was conducted in Universitas Singaperbangsa Karawang from June 26th 2010 through July 24th 2010. The students involving in this program were given a material that has been adjusted in accordance with the curriculum applied in formal school by using a variety of teaching methodology to make a contented atmosphere. Moreover, the students were obliged to have pre-test and post-test. The results of both tests show that there is 30.48% increment and it indicates that this community service has successfully yet slightly improved the students’ skills in English that has played a crucial role in education world in Indonesia.